2013
DOI: 10.1126/scisignal.2003994
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinases Fall into Distinct Classes Based on Their Inferred Signaling Networks

Abstract: Although many anticancer drugs that target receptor tyrosine kinases (RTKs) provide clinical benefit, their long-term use is limited by resistance that is often attributed to increased abundance or activation of another RTK that compensates for the inhibited receptor. To uncover common and unique features in the signaling networks of RTKs, we measured time-dependent signaling in six isogenic cell lines, each expressing a different RTK as downstream proteins were systematically perturbed by RNA interference. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 56 publications
4
49
0
2
Order By: Relevance
“…This suggests that alternative molecular pathways of escape may also arise that drive tumor growth independent of HRG and ER inhibition. This is consistent with the signaling redundancy that exists among RTKs and that allows for compensatory signaling upon targeted inhibition (10,37,38). Identifying these compensatory signaling mechanisms remains the focus of future studies.…”
Section: Discussionmentioning
confidence: 49%
“…This suggests that alternative molecular pathways of escape may also arise that drive tumor growth independent of HRG and ER inhibition. This is consistent with the signaling redundancy that exists among RTKs and that allows for compensatory signaling upon targeted inhibition (10,37,38). Identifying these compensatory signaling mechanisms remains the focus of future studies.…”
Section: Discussionmentioning
confidence: 49%
“…75,89 For example., models of dynamic changes in signalling networks of receptor tyrosine kinases (RTK) families have facilitated the classification of RTKs and their network activation and led to the identification of points of intervention to delay or overcome drug resistance. 78,90 Furthermore, Komurov et al, 91 used a novel network-based analysis of gene expression and proteomics coupled to ErbB2-positive patient survival data, and showed that in breast tumours with acquired resistance to lapatinib, the drug was still able to block EGFR/ErbB2 signalling, but that upregulation of glucose metabolism, unfolded protein response, and endoplasmic reticulum (ER) stress pathways mitigated the ability of lapatinib to induce cell death, suggesting that coordinated targeting of metabolic networks and signalling networks has the potential to improve patient outcomes. 91,92 Beckman et al .…”
Section: Cancer Systems Biology Approachesmentioning
confidence: 99%
“…Amplifications of Ras/Raf are present in cancer cells continuously stimulated by growth factors such as HER-soluble ligands, autocrine signaling or constitutively activated mutant receptors. RAS gene mutations have been found in colon (45%), pancreatic (90%), ovarian (30%) and papillary thyroid (60%) carcinomas, and in 15% of melanomas and 35% of non-small-cell lung cancers (NSCLC) (Eccles, 2011;Wagner et al, 2013).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…These pathways affect the growth and the cell cycle, reorganization of cytoskeleton and apoptosis (and its inhibition), migration, invasiveness, differentiation, angiogenesis, transcription, and other processes that lead to the formation and progression of malignant tumors (Yarden, Sliwkowsk, 2001;Citri, Yarden, 2006;Red Brewer et al, 2009;Wagner et al, 2013;Park, 2014).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation